Bisphenol A exposure and associations with obesity among adults: a critical review. Issue 10 (14th October 2014) - Oppeneer, Sarah J; Robien, Kim
Abstract: Objective: To review the literature on bisphenol A (BPA) exposure and obesity in human populations. Design: Systematic review of the literature via searches of PubMed, EMBASE, Web of Science and reference lists for articles published to 1 August 2014. Setting: China, Italy, Japan, Republic of Korea, Sweden, UK, USA. Subjects: Adults (≥18 years). Results: Eighteen articles were identified and included in the review. Twelve studies included secondary evaluations of BPA exposure and BMI, and six studies evaluated body composition as the primary outcome. All analyses were cross-sectional and no study included in the review received a positive quality rating (twelve negative, six neutral). Eight studies observed a statistically significant positive association between urinary or serum BPA levels and BMI, and ten studies observed no association. Studies where BMI was a primary outcome and studies of neutral quality were more likely to observe an association. Conclusions: Study results are conflicting and significant methodological issues limit the ability to draw conclusions from these studies. Prospective studies that measure BPA exposure and changes in body weight and composition are needed to establish temporality, causality and the direction of any observed associations.